2008
DOI: 10.1038/modpathol.2008.124
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous genetic profiles in soft tissue myoepitheliomas

Abstract: Myoepithelioma, mixed tumor and parachordoma are uncommon soft tissue tumors thought to represent morphological variants of a single tumor type. The genetic basis of these neoplasms is poorly understood. However, they morphologically resemble mixed tumor of the salivary glands (also known as pleomorphic adenoma), a tumor characterized by deregulated expression of PLAG1 or HMGA2. To evaluate a possible genetic relationship between these soft tissue and salivary gland tumors, PLAG1 expression levels and the geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 25 publications
2
50
0
Order By: Relevance
“…[28][29][30] Although some soft tissue myoepitheliomas may demonstrate PLAG1 rearrangement, 31 many soft tissue myoepitheliomas and mixed tumors of the skin have an EWSR1 gene rearrangement, which is not present in mixed tumors of salivary glands. 12,27,[32][33][34] Myoepithelioma of bone is rare; 9 cases have been reported in the literature (Table 3). 16,18,20,27 Combining our cases with those previously described, men and women are affected at a ratio 5:4, and the age range is 14 to 55 (mean, 32) years.…”
Section: Discussionmentioning
confidence: 95%
“…[28][29][30] Although some soft tissue myoepitheliomas may demonstrate PLAG1 rearrangement, 31 many soft tissue myoepitheliomas and mixed tumors of the skin have an EWSR1 gene rearrangement, which is not present in mixed tumors of salivary glands. 12,27,[32][33][34] Myoepithelioma of bone is rare; 9 cases have been reported in the literature (Table 3). 16,18,20,27 Combining our cases with those previously described, men and women are affected at a ratio 5:4, and the age range is 14 to 55 (mean, 32) years.…”
Section: Discussionmentioning
confidence: 95%
“…Elevated activity of PLAG1 primarily results from recurrent translocations that lead to upregulation of the PLAG1 gene (Kas et al, 1997, 1998; Voz et al, 1998, 2000b; Astrom et al, 1999). Contrary to the extensive cytogenetic and molecular genetic studies of pleomorphic adenomas over the course of the past 2.5 decades (Mark and Dahlenfors, 1986; Bullerdiek et al, 1993; Kas et al, 1997, 1998; Voz et al, 1998, 2000a, 2000b, 2004; Astrom et al, 1999; Asp et al, 2006; Van et al, 2007), few studies have focused on exploring the genetics of myoepithelial tumors in soft tissues (Hallor et al, 2008; Antonescu et al, 2010). This is partly because of the novelty of the myoepithelioma concept in soft tissue (where there is no evident normal cellular counterpart), and partly due to the rarity of these tumors at extra-salivary sites and the difficulty in classifying them.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, a different study showed that cutaneous mixed tumors could also harbor EWSR1 abnormalities (Flucke et al, 2011). No HMGA2 gene abnormalities were discovered so far in soft tissue or bone ME tumors (Hallor et al, 2008; Antonescu et al, 2013). …”
Section: Discussionmentioning
confidence: 99%